Demographic analysis of occupational accident occurrence in manufacturing industry - Mohd. Rohani, Jafri (2015)
The objective of this paper is to analyze the demography aspect of occupational accident occurrence in Malaysia for manufacturing industry. High accident rate would give an adverse effect not only to the victims and their family but also to the organization as well. This study analyses various type of occupational accidents which limited to temporary disability with more than one day sick leave and cases recorded range between 2008 and 2013. The data is gathered from six different sectors within manufacturing industry by using local specific approach. Information related to each accident is obtained by checking past occupational accident record and interviewing site safety officer in charge, human resource representative, site supervisor and fellow workers. There are 342 cases in total have been gathered during data collection process before data analysis phase took place. This study provides a better perspective regarding to occupational accident occurrence to interested stakeholder such as enforcement body, occupational health and safety practitioner and company management itself. The findings from this study can be used to draft necessary preventive measures in order to provide safe working environment which can give significant impact through reduction of occupational accidents in the future.